REAL‐world clinical effectiveness of ivacaftor therapy in the first 24 months in two infants with cystic fibrosis and different gating mutations—A case report. Issue 2 (10th February 2022) - Fuchs, Teresa; Appelt, Dorothea; Niedermayr, Katharina; Ellemunter, Helmut
Abstract: This study summarizes efficacy of ivacaftor treatment in 2 infants in a real‐world setting. A distinct decline of sweat chloride and lung clearance index plus increase in fecal elastase was seen. The results underline the early and sustainable effect and give cause for discussing whether a reduction in standard cystic fibrosis therapy is possible. Abstract : Ivacaftor therapy in infants with cystic fibrosis is clearly disease modifying, demonstrated by sweat chloride, lung clearance index, and fecal elastase. Therefore, classical therapy recommendations could be reconsidered. Also, the further achievement of internationally defined anthropometric targets could be discussed.